Constitutional Limits On The Application Of The Principle Of Non-renounceability Of Rights In Labor Matters. A Theoretical Approach - Rodríguez Martínez, Gonzalo Javier (Ius Humani. Jornal do direito, 2024)
The principle of non-waivability of rights in peruvian labor jurisdictions has been the subject of intense academic debates. This study explores the interaction between non-waivability of rights and normative temporality rules concerning labor rights enshrined in the 1993 Constitution. It argues that a correct interpretation, considering the theory of accomplished facts, encourages formal employers to create jobs in the Peruvian economy. Furthermore, it examines the jurisprudential application of the non-waivability principle in labor proceedings, emphasizing Law 29497 and its impact on conciliation agreements.